An introduction to health psychology - Morrison, Val, 1961-; Bennett, Paul, 1955- (Harlow, Essex ; New York : Pearson Addison Wesley, 2012)
An Introduction to Health Psychology, Third edition gives you a comprehensive and lively introduction to this interesting field. Retaining the highly praised approach of the first and second editions, each chapter outlines and describes the theory and research before moving on to explore applications and intervention practice. The primary goals of health psychologists are to describe, predict and intervene, and this process is reflected in the book. Useful features are included to support your learning, such as research focus boxes, applications boxes and engaging case studies. Bringing together core topics and current debates, An Introduction to Health Psychology, Third edition is ideal for students on health psychology modules, and for those studying in related fields such as health and social care or nursing.
Keywords: Psychologie -- Gezondheidszorg